HOLY INSTITUTION, UNHOLY REALITY: ANALISIS WACANA KRITIS TERHADAP SUDUT PANDANG VICE INDONESIA TENTANG KEKERASAN SEKSUAL PESANTREN - Maulidia, Zulia Khikmatul; Ariani Arimbi, Diah; Endah Srimulyani, Nunuk (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article discusses how VICE Indonesia, through a documentary video titled “Breaking the Chain of Sexual Violence in Islamic Boarding Schools,” addresses the issue of sexual violence in religious education environments. The researchers used Fairclough's Critical Discourse Analysis (CDA) approach to examine how the language used in the video could shape public opinion. The analysis was conducted in three parts: textual analysis, discursive practice, and social practice. The research results show that VICE Indonesia presents the victims as the main characters who bravely speak out, and highlights the patriarchal culture as the main cause of sexual violence. This video also combines several perspectives such as law, religion, and the feminist movement to provide a broader picture of the issue. VICE Indonesia seems to support the feminist view that seeks equality between men and women, especially in Islamic boarding schools. This documentary not only criticizes religious institutions but also invites society to rethink religious values that have long been considered untouchable. This research shows that media such as documentaries can be an important tool for raising awareness and encouraging social change.